Genetic variation among Glomerella cingulata isolates from different Lauraceae hosts - Scheper, R.W.A.; Timudo-Torrevilla, O.E.; Rees-George, J.; Everett, K.R. (New Zealand Plant Protection, 2008)
Four populations of Glomerella cingulata 20 isolates each were sampled from avocado (Perseae americana) fruit from orchards throughout New Zealand and from Queensland Australia and from leaves of Beilschmeidia tawa and Beilschmeidia taraire in Hawkes Bay and the Waitakere Ranges respectively Among 80 isolates 44 different colony morphologies were identified with only three of these occurring in more than one of the four populations The population from B taraire showed less variation in colony morphology than did the other populations with a Shannon and Weaver information statistic H of 047 compared with 071 to 093 More of the diversity occurred within the populations (64) than between them (36) Sequence analysis of the ITS region using maximumparsimony identified two clades among the isolates with all isolates from the native New Zealand trees clustering in one clade and all avocado isolates in the other Some variation was detected within the clades although all isolates from B taraire had identical sequences This study indicates that G cingulata populations from avocado and native trees may represent genetically isolated populations that have evolved separately To identify geographic origin of fungal populations from avocado a different DNA sequence with more variation is required